Analysis of the Effect of Posterior Lateral Malleolus Plate Fixation on the Curative Effect and Mechanical Stability of Complex Ankle Fractures. (6th June 2022) - Zha, Junpu; Zhang, Guolei; Zhang, Jingtao; Wang, Xiaoqing; Li, Jie; Di, Jun
Abstract : This paper investigates the effect of lateral and posterior 1/3 tubular plate bone plate fixation on the curative effect, wound healing, and mechanical stability of complex ankle fracture. 80 patients with complex ankle fractures treated in our hospital from January 2018 to July 2020 are selected for the study, and 80 patients are randomly divided into posterior fixation group and lateral fixation group according to the number table method, with 40 patients in each group. Patients in the posterior malleolus fixation group are treated with posterior lateral malleolus plate fixation, and patients in the lateral malleolus fixation group are treated with lateral malleolus plate fixation. The differences in efficacy, mechanical stability, wound healing, visual analog scale (VAS) pain score, and American Association of Foot and Ankle Surgery (AOFAS) ankle function are compared. The subjects are followed up for 6 months until January 2022. In patients with complex ankle fracture, 1/3 tubular plate osteoplate fixation in the posterior lateral malleolus can improve clinical efficacy and mechanical stability, which is helpful to promote incision healing and reduce the risk of complications. The 1/3 tubular plate osteoplate fixation in the posterior lateral malleolus is worthy of clinical promotion and application.